2011
DOI: 10.1007/s12298-011-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Proline induces heat tolerance in chickpea (Cicer arietinum L.) plants by protecting vital enzymes of carbon and antioxidative metabolism

Abstract: Chickpea is a heat sensitive crop hence its potential yield is considerably reduced under high temperatures exceeding 35°C. In the present study, we evaluated the efficacy of proline in countering the damage caused by heat stress to growth and to enzymes of carbon and antioxidative metabolism in chickpea. The chickpea seeds were raised without (control) and with proline (10 μM) at temperatures of 30/25°C, 35/30°C, 40/35°C and 45/40°C as day/ night (12 h/12 h) in a growth chamber. The shoot and root length at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
84
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 66 publications
13
84
1
3
Order By: Relevance
“…Lowest CSI was recorded for the varieties PES400 (67.65 %) and VR708 (70.07 %), which indicates a susceptible character to drought. H 2 O 2 is an important signaling molecule and its levels are kept under check by a battery of H 2 O 2 metabolizing enzymes (Kaushal et al 2011). Any increase in H 2 O 2 has severe consequences for the affected cell.…”
Section: Resultsmentioning
confidence: 99%
“…Lowest CSI was recorded for the varieties PES400 (67.65 %) and VR708 (70.07 %), which indicates a susceptible character to drought. H 2 O 2 is an important signaling molecule and its levels are kept under check by a battery of H 2 O 2 metabolizing enzymes (Kaushal et al 2011). Any increase in H 2 O 2 has severe consequences for the affected cell.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, application of different osmoregulators as glycinebetaine (GB) or proline had a significant role on plant growth promotion and seed yield under normal or stress conditions as observed in some crops e.g., maize (Yang and Lu, 2006;Kaya et al,2013;Reddy et al, 2013),canola (Dawood and Sadak, 2014), rice (Mohammed and Tarpley, 2011), wheat (Raza et al, 2014), chickpea ( Kaushal et al,2011) and faba bean (Taie et al, 2013;.…”
Section: Physiological Role Of Osmoregulatorsmentioning
confidence: 99%
“…There are several reports indicated that abiotic stress conditions trigger the accumulation of proline in plant tissues (Kaushal et al,2011;Hayat et al, 2012;Slama et al, 2014). Moreover, exogenous application of proline caused increases in its endogenous levels in plant tissues subjected to water stress conditions and induced plant tolerance (Ashraf and Foolad, 2007;Ali et al, 2008).…”
Section: Prolinementioning
confidence: 99%
See 1 more Smart Citation
“…Proline, an amino acid, which is increased in response to diverse types of abiotic stresses (Kaushal et al, 2011), has several roles in turgor generation, osmotic adjustment, storage of carbon and nitrogen, and cellular redox potential. Furthermore, proline could maintain the enzyme structure and activity (Kaushal et al, 2011) and thus protect membrane integrity (Hayat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%